Wind-induced responses and equivalent static design method of oval-shaped arch-supported membrane structure. Issue 213 (June 2021) - Kandel, Arjun; Sun, Xiaoying; Wu, Yue
Abstract: This paper presents the wind-induced responses and wind resistant design method of arch-supported membrane structure. Series of rigid model wind tunnel tests are carried out to record wind pressure data on the roof surface of experimental models. Random vibration time history analysis is employed to get wind-induced responses. Geometric nonlinearity is taken into account in dynamic analysis. Effects of different factors such as wind velocity, wind direction, arch span, rise-span ratio, and membrane prestress on peak wind-induced responses are presented meticulously. Displacement, membrane stress, internal force of cable and abutment reaction are analyzed to study the peak responses of structure. This study considers the influence of boundary wall by conducting wind tunnel tests on both enclosed and open models. Results show that peak responses increase significantly as wind velocity and/or arch span increase. The performance of membrane structures can be enhanced by increasing membrane prestress, but the effect is quite small. Similarly, responses increase with rise-span ratio, but the rate of increment is not constant. Effect of the boundary wall depends significantly on wind direction and rise-span ratio. Additionally, this paper proposes the concept of equivalent static design method based on gust loading factor and nonlinear adjustment factor. Highlights: Wind tunnel tests on oval-shaped arch-supported membrane structures are carried out. Wind-induced responses of membrane roof under wind excitation are presented. Effects of different load and structural parameters on peak responses are studied. Based on the peak responses, arch span is found to be the most influential parameter. Equivalent static design method based on gust loading and non-linear adjustment factors is proposed.